Answer:
x= 2, y= 1
Step-by-step explanation:
To solve by elimination method, start by labelling the two given equations.
4x -y -7= 0 -----(1)
4x +3y -11= 0 -----(2)
Let's now eliminate the x variable by subtracting one equation from the other.
(1) -(2):
4x -y -7 -(4x +3y -11)= 0 -0
Expand:
4x -y -7 -4x -3y +11= 0
Simplify:
-4y +4= 0
+4 on both sides:
4= 4y
Divide both sides by 4:
y= 1
Substitute into (1) to find value of x:
4x -1 -7= 0
4x -8= 0
4x= 8
Divide both sides by 4:
x= 2
For more examples on solving by elimination, do check out the following!
https://brainly.com/question/12691830